Targeted intracellular degradation of SARS-CoV-2 via computationally optimized peptide fusions - Pranam Chatterjee (Nature Portfolio, 2020)
Pranam Chatterjee et al. present a novel computational platform for engineering peptide fusions that bind to the SARS-CoV-2 spike protein and tag it for proteasomal degradation. They experimentally validate an optimal variant in human cells, showing that it inhibits production of infection-competent virus.